Uneducated guesses : using evidence to uncover misguided education policies - Wainer, Howard (Princeton University Press, 2011)
Uneducated Guesses challenges everything our policymakers thought they knew about education and education reform, from how to close the achievement gap in public schools to admission standards for top universities. In this explosive book, Howard Wainer uses statistical evidence to show why some of the most widely held beliefs in education today--and the policies that have resulted--are wrong. He shows why colleges that make the SAT optional for applicants end up with underperforming students and inflated national rankings, and why the push to substitute achievement tests for aptitude tests mak.